2019
DOI: 10.1007/s10453-018-09557-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial bioaerosol concentration and size distribution in the selected animal premises in a zoological garden

Abstract: Currently, there are almost no studies concerning bioaerosol and particulate matter levels in animal enclosures of zoos. Numerous air contamination sources can be found there, and zoos are both working environments and popular tourist objects. The aim of this study was to assess bacterial aerosol levels in premises for animals (giraffes, monkeys, pheasants and ostriches) of the Kraków Zoo. Bioaerosol samples were collected using six-stage Andersen impactor to assess the concentration and size distribution of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…There have been numerous studies on microbial aerosol in animal production premises (e.g., Dutkiewicz et al 1994;Jacobson et al 2003;Ławniczek-Wałczyk et al 2013;Budzińska et al 2014;Matković et al 2007Matković et al , 2009Millner 2009;Sowiak et al 2012;Viegas et al 2013) or in farming environment (e.g., Karwowska 2005;Douglas et al 2018), but none of those referred to non-production facilities, such as zoological gardens. In a previous study, Grzyb and Lenart-Boroń (2019) investigated the concentration and size distribution of bacterial aerosol in some premises of a Zoological Garden in Kraków and indicated that animals can be a significant source of bacterial bioaerosol components, but the levels of bioaerosol may vary significantly depending on the animals kept in the premises. Moreover, the respirable fraction of bioaerosol was predominant, reaching 70% of the total fraction in some cases, which indicates possible health threats to the people exposed.…”
mentioning
confidence: 99%
“…There have been numerous studies on microbial aerosol in animal production premises (e.g., Dutkiewicz et al 1994;Jacobson et al 2003;Ławniczek-Wałczyk et al 2013;Budzińska et al 2014;Matković et al 2007Matković et al , 2009Millner 2009;Sowiak et al 2012;Viegas et al 2013) or in farming environment (e.g., Karwowska 2005;Douglas et al 2018), but none of those referred to non-production facilities, such as zoological gardens. In a previous study, Grzyb and Lenart-Boroń (2019) investigated the concentration and size distribution of bacterial aerosol in some premises of a Zoological Garden in Kraków and indicated that animals can be a significant source of bacterial bioaerosol components, but the levels of bioaerosol may vary significantly depending on the animals kept in the premises. Moreover, the respirable fraction of bioaerosol was predominant, reaching 70% of the total fraction in some cases, which indicates possible health threats to the people exposed.…”
mentioning
confidence: 99%
“…The comparison of the research results obtained in the course of the examinations conducted in the zoo in Kraków (Grzyb and Lenart-Boroń 2019 ) with those delivered as a result of measurements taken in Chorzów revealed that concentrations recorded in the shelters for giraffes in Kraków zoo were 12 times lower, while in rooms for monkeys about 3 times higher. Due to the fact that the facilities for giraffes in both zoos are of the same age, the difference in bioaerosol concentration may be the result of different area per one animal (Kraków: 244 m 2 ; Chorzów: 66.8 m 2 ).…”
Section: Discussionmentioning
confidence: 92%
“…Microbial cells are usually associated with dust particles, what facilitates penetration of microorganisms with the air (bacteria—in the form of cells and spores, molds as spores). Previous research has shown that microbial aerosol concentrations were relatively high in the animal facilities (Sowiak et al 2012 ; Grzyb and Lenart-Boroń 2019 ). The concentrations of airborne bacteria in rooms intended to house animals are usually much higher than in human dwellings.…”
Section: Introductionmentioning
confidence: 96%
“…The large positive deviation of the DustTrak by a factor of about 1.5 is not surprising. Previous studies have found that different DustTrak models over-recorded PM values by a factor of 1.2−3 (Chung et al, 2001;Grzyb and Lenart-Boron, 2019;Heal et al, 2000;Kingham et al, 2006;Liu et al, 2017;McNamara et al, 2011;Wallace et al, 2011;Yanosky et al, 2002) depending on the aerosol properties. It has been suggested that the "over-estimation is a simple calibration issue in which differences between the optical properties of the manufacturer's factory calibration PM (Arizona Road Dust) and the PM under study explained the uniform relative errors recorded" (Kingham et al, 2006).…”
Section: Intercomparision Of Automated Pm Monitors With the Referencementioning
confidence: 99%
“…This requires long and expensive testing campaigns at multiple sites during different times of the year in an attempt to include all representative meteorological conditions and the temporal and spatial variations of the ambient air composition. Portable and cost-effective PM monitors, such as the DustTrak (TSI Inc., USA) and Fidas Frog (Palas, Hermany), which are mostly employed for industrial/occupational hygiene surveys (Asbach et al, 2018;Davison et al, 2019;Grzyb and Lenart-Boron, 2019), outdoor (Kingham et al, 2006;Viana et al, 2015;Wallace et al, 2011) and indoor (Chowdhury et al, 2013;Manibusan and Mainelis, 2020;Zhou et al, 2016) air quality investigations, process or emissions monitoring (Al-Attabi et al, 2017;Crilley et al, 2012;Grall et al, 2018;McNamara et al, 2011) and aerosol research studies, do not necessarily go through equivalence testing. Instead, they are often calibrated in the laboratory with simple model aerosols, e.g.…”
Section: Introductionmentioning
confidence: 99%